The Effect Of immune molecules in protection against COVID 19 - Njum, Ali Anok; Rima N. Hassan, (International Journal of Psychosocial Rehabilitation, 2020)
project attempts to estimate the manifestation of stimulated indicators on pBL ,as the manifestation of CD45 & CD74 in patients infected with COVID19 assessment of TNF-α and IL-8 serum ranks in patients with COVID 19 , associate the consequences of pBL –stimulation indicators appearance and serological valuationof TNF-α &IL-8 using multiple infection phases. A total of (24) positive patients for COVID19 were screened for this study .Patients attended general lab. of Al-Muthanna province , because of abdominal pain ,pulmonary distress , fever and coughing any samples expressed positive for COVID19 directly choose to show level of TNF-α & IL-8 in serum of patient and show expression of CD45 and CD74 in pBL in HCV patients. Results showed that serum samples were analyzed for IL-8 & TNF-α by ELISA , showed highly significant increases (p